Serum uric acid reduction through SGLT2 inhibitors: evidence from a systematic review and meta-analysis - Yang, Shiwen; Hu, Qiaozhi; Liu, Kexin; Xiao, Binjie; Zhang, Bofei; Su, Na (Frontiers in Pharmacology, 2025)
BackgroundElevated serum uric acid (SUA) is strongly associated with adverse clinical outcomes. Sodium-glucose-cotransporter-2 (SGLT2) inhibitors not only lower blood glucose levels but also reduce UA. However, comparative data on the SUA-lowering effects among different SGLT2 inhibitors remain sparse, hindering evidence-based drug selection. This study aimed to systematically evaluate the effects of various SGLT2 inhibitors on SUA.MethodsWe searched the Cochrane Central Register of Controlled Trials (Ovid SP), Embase (Ovid SP), PubMed, and ClinicalTrials.gov up to March 2024 for randomized controlled trials (RCTs) evaluating SGLT2 inhibitors in patients with or without type 2 diabetes mellitus (T2DM). The primary outcome was the change in SUA levels compared with placebo. Data were analyzed using Review Manager 5.4. Pooled mean differences (MDs) for continuous outcomes (SUA change) and relative risk (RR) for dichotomous outcomes (gout incidence) were calculated. Study quality was evaluated using the Cochrane Risk of Bias tool (RoB 2), and the overall evidence quality was evaluated using the GRADE approach.ResultsA total of 51 RCTs were included in the meta-analysis. The SUA levels were significantly lower in all SGLT2 inhibitors groups than in the placebo groups. SGLT2 inhibitors have superior efficacy in lowering SUA levels compared with placebo [MD = −32.14 μmol/L, 95% CI (−35.96 to −28.31); P < 0.001]. Subgroup analysis showed empagliflozin achieved the greatest reduction in SUA [MD = −45.61 μmol/L, 95% CI (−52.26 to −38.97); P < 0.00001], while sotagliflozin had the least effect [MD = −13.72 μmol/L, 95% CI (−19.16 to −8.29); P < 0.00001]. The GRADE profiles indicated low-quality evidence for reduction in SUA levels. However, there was no difference in the incidence of gout between the two groups [RR = 0.96, 95% CI (0.77–1.21), P = 0.75].ConclusionSGLT2 inhibitors demonstrated greater SUA reduction than placebo, highlighting their potential as multifactorial therapies in high-risk populations.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/#loginpage, identifier CRD42023458993.